The Development of Knowledge and Appreciation in Lanna Dancing Art among Students in Provincial Secondary School in Lamphun and Lampang Province - Changkhaokam, Udomgarn; Patanapongsa, Narinchai (Journal of Cultural Approach, 2015)
This research was divided into two phases: the survey and the quasi-experimental research. Phase 1 was the survey research which aimed at generating a model for developing knowledge and appreciation in Lanna Dancing Art among students in provincial secondary school in Lamphun and Lampang Provinces. The number of samples employed in this phase was 20 participants; including dancing art teachers in provincial secondary schools, Lanna Dancing artists, local scholars, and students in provincial secondary school. These participants were invited to attend the participative meeting to brainstorm the factors which hindered the knowledge and appreciation in Lanna Dancing Art. The findings of the study showed that there were two factors which affected the knowledge and the appreciation in Lanna Dancing Art; namely, internal factor (i.e. motivation) and external factors (i.e.social support, appropriate role models, media and technology influences). The findings of this phase were employed to generate a model for the development of knowledge and appreciation in Lanna Dancing Art. Phase 2 was the quasi-experimental research which aimed at the experimentation of the model derived from the first phase of the study. The number of samples used in this Phase was 160 students in provincial secondary school in Lamphun and Lampang Provinces, which divided into two groups, namely, 80 students for the experimental group and 80 students for the controlled group. The findings reveal that the mean scores of the knowledge and appreciation in Lanna Dancing Art of the students in the experimental group prior to and after the experiment were statistically significant differences. That is the level of knowledge and appreciation in Lanna Dancing Art of the students who participated in the development activities were higher than those who did not to participate in such activities. Therefore, it can be concluded that the knowledge and appreciation in Lanna Dancing Art can be developed by the model of the development which is presented in this study.